The Impact of Flexible Work Policies on Gen Z Employee Satisfaction and Retention: A Multi-Industry Analysis - Eli Retnowati; Sunardi Ginting; Asnawi; Klemens Mere; Ahmad Jumarding (Dinasti Publisher, 2024)
The adoption of flexible work policies has emerged as a pivotal strategy in contemporary workplaces, particularly affecting Generation Z (Gen Z) employees. This study investigates the impact of flexible work policies on Gen Z employee satisfaction and retention across multiple industries. Drawing on a comprehensive literature review, this research synthesizes existing findings to identify key factors influencing Gen Z's perception of flexible work arrangements, such as remote work options, flexible hours, and autonomy in task management. The analysis explores how these policies contribute to enhanced job satisfaction and reduced turnover intentions among Gen Z workers. Furthermore, this study examines industry-specific variations in the implementation and effectiveness of flexible work policies, considering sectors ranging from technology to healthcare. Insights gained from this research not only underscore the significance of flexibility in contemporary workforce management but also provide practical recommendations for organizations seeking to optimize Gen Z employee satisfaction and retention strategies.